The Effect of Sensitivity Training on the Self-Concept of Vocational Students of Donmuang Technical College, Bangkok, Thailand - Chantana, Sujitra (1993)
The study investigates the influence of "Sensitivity" training on the self concept of Donmuang Technical College's students in Bangkok, Thailand. One hundred and sixty third-year students of certificate level were divided at random in to two groups: experimental group and the control group. The research design was pretestpost test control group design. Each group comprised 80 students. An instrument developed by Luxpetch's self concept Rating Scale (1984) was administered to both group sat the beginning and again at the end of the sensitivity training. Analyses were made by frequencies, T-test and Chi-square test carried out on the experimental group and control group. The major findings were: 1. The students who had under gone sensitivity training had higher self-concept in terms of perceive self, ideal self and emotional adjustment than those who had not. 2. There was no significant relation ship between self-concept and gender as well as parents' occupation on the control group. Where as a significant difference was found between gender and perceived self on the experimental group.